An Investigation of Flow in Nozzle Hole of Dimethyl Ether. (November 2015) - Kato, M; Yokota, T; Weber, J; Gill, D
Abstract: For over twenty years, DME has shown itself to be a most promising fuel for diesel combustion. DME is produced by simple synthesis of such common sources as coal, natural gas, biomass, and waste feedstock. DME is a flammable, thermally-stable liquid similar to liquefied petroleum gas (LPG) and can be handled like LPG. However, the physical properties of DME such as its low viscosity, lubricity and bulk modulus have negative effects for the fuel injection system, which have both limited the achievable injection pressures to about 500 bar and DME's introduction into the market. To overcome some of these effects, a common rail fuel injection system was adapted to operate with DME and produce injection pressures of up to 1000 bar. To understand the effect of the high injection pressure, tests were carried out using 2D optically accessed nozzles. This allowed the impact of the high vapour pressure of DME on the onset of cavitation in the nozzle hole to be assessed and improve the flow characteristics.